Structural and functional characterization of two novel peptide toxins isolated from the venom of the social wasp Polybia paulista - Souza, B. M.; Mendes, M. A.; Santos, L. D.; Marques, M. R.; Cesar, LMM; Almeida, RNA; Pagnocca, F. C.; Konno, K.; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2005)
Two novel inflammatory peptides were isolated from the venom of the social wasp Polybia paulista. They had their molecular masses determined by ESI-MS and their primary sequences were elucidated by Edman degradation chemistry as:Polybia-MPI: I D W K K L L D A A K Q I L-NH2 (1654.09 Da),Polybia-CP: I L G T I L G L L K S L-NH2 (1239.73 Da).Both peptides were functionally characterized by using Wistar rat cells. Polybia-MPI is a mast cell lytic peptide, which causes no hemolysis to rat erythrocytes and presents chemotaxis for polymorphonucleated leukocytes (PMNL) and with potent antimicrobial action both against Gram-positive and Gram-negative bacteria. Polybia-CP was characterized as a chemotactic peptide for PMNL cells, presenting antimicrobial action against Gram-positive bacteria, but causing no hemolysis to rat erythrocytes and no mast cell degranulation activity at physiological concentrations. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Polybia paulista; hymenoptera insect; polycationic peptide; wasp venom; mastoparans; chemotactic peptides